Promosi Cashback Pada Ovo dan Harga dalam Mempengaruhi Perilaku Konsumen - Amelia, Wan Rizca; Salqaura, Siti Alhamra; Safina, Wan Dian (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This article aims to find out whether promotions in the form of cashback and prices can influence consumer behavior which is focused on FEB UMA students. This problem is focused on changes in consumer behavior who make payments using OVO at merchants who have collaborated. The cashback referred to in this research can be in the form of OVO Points which can later be used for shopping, ordering food, or ordering online transportation. The type of research used is associative quantitative research. The population in the research was 272 students from the Faculty of Economics and Business, University of Medan Area Management Study Program and it is known that the number of samples to be studied was 73 respondents. Data collected through questionnaires. The data analysis technique uses multiple regression. This study concludes that based on the results of the hypothesis test (t test) the Cashback promotion variable has a positive and significant effect on consumer behavior and price has a positive and significant effect on consumer behavior. Using a simultaneous test (f test), it was concluded that cashback promotions and prices had a positive and significant effect on consumer behavior.